Active DNA demethylation mediated By GADD45β is essential during G-CSF triggered granulocytic differentiation - Mir, Perihan; Klimiankou, Maksim; Aghaallaei, Nargessadat; Findik, Betuel; Thalheimer, Frederic; Wingert, Susanne; Rieger, Michael A.; Thumberger, Thomas; Zeidler, Cornelia; Bajoghli, Baubak; Welte, Karl; Skokowa, Julia (Blood, 2019)
Congenital neutropenia (CN) is a bone marrow failure syndrome which is characterized by a maturation arrest of myeloid progenitors in the bone marrow. The pathomechanism leading to the defective granulopoiesis in CN patients is not fully elucidated.We recently reported the inability of G-CSF to induce GADD45β (Growth arrest and DNA damage-inducible 45, beta) expression in myeloid progenitors of CN patients harboring ELANE or HAX1 mutations. GADD45β functions as stress sensor downstream of myeloid cytokines and is important in murine stress-induced hematopoiesis. Moreover, we could show that C/EBPα, which is severely diminished in CN cells, binds and activates the GADD45β promoter.Importantly, rescue of the GADD45β expression in ELANE-CN HSPCs by lentivirus-based transduction of GADD45B cDNA restored defective granulocytic differentiation compared to control transduced cells. Transduction of mouse HSCs with ectopic Gadd45β resulted in drastic decrease of immature and increase of mature myeloid cells over time. Colony forming unit (CFU) and CFU re-plating assay showed that Gadd45β overexpressing mouse HSCs exhibit lower proliferation capacity.To determine the role of GADD45β in vivo, we performed CRISPR/Cas9 knockout of gadd45bb in wild type and Tg(mpo:gfp) zebrafish embryos, in which GFP expression is activated by the mpo promoter. We found that gadd45bb-deficiency lead to dramatic reduction in neutrophil numbers as assessed by counting mpo+ cells. Ectopic expression of G-CSF using a heat-inducible system increased the number of mpo+ cells in gadd45bb crispants but not to a level similar to wild type zebrafish expressing G-CSF.GADD45 proteins are implicated in active DNA demethylation by recruiting the DNA repair machinery to specific sites in the genome to convert 5-methylcytosine into unmethylated cytosine. Nothing is known about active DNA demethylation downstream of G-CSF and the role of GADD45β in this process. We sought to unveil whether GADD45β mediates G-CSF triggered myeloid differentiation by specific gene demethylation. To address this, we performed RNA sequencing and DNA methylation analysis of wild type (WT) and GADD45β knockout (KO) CD34+ HSPCs treated or untreated with G-CSF for 72h. The RNA-seq analysis demonstrated a GADD45β-dependent upregulation of genes which play a role in neutrophil differentiation and function as for instance RXRA, ITGAM (CD11b), FPR1/2, MEFV and BATF upon G-CSF treatment. Strikingly, these genes were also upregulated in promyelocytes of healthy controls upon G-CSF treatment, but not in CN patient promyelocytes. Genomatix-based gene ontology analysis of significantly upregulated genes in the G-CSF-treated WT but not GADD45β KO group displayed that diseases associated with this expression signature included neutropenia, leukocyte disorders and AML. Motif enrichment analysis of GADD45β-responsive genes predicted mainly motifs for myeloid-specific transcription factors (e.g. RXRA, SPI1 and C/EBPβ) to be enriched.Finally, DNA methylation analysis revealed significant differences in methylation pattern between GADD45β WT and KO groups upon G-CSF treatment. In WT cells G-CSF caused the hypomethylation of 13.516 CpGs and in GADD45β KO cells, only 8.440 CpGs were hypomethylated. Methylation changes between WT and KO groups mainly occurred in myeloid-specific genes, e.g. ELANE, MPO, CSF3R and AZU1. We also identified myeloid differentiation-related genes of which mRNA expression was regulated by GADD45β-mediated DNA demethylation, as for instance RXRA, CXCR1, MEFV, FPR2 and SERPINA1. Importantly, diseases associated with the defective gene demethylation downstream of G-CSF were neutropenia, immune system diseases, pre-leukemia and AML, as assessed by Genomatix analysis.Taken together, we report for the first time the importance of GADD45β-dependent DNA demethylation for human and zebrafish G-CSF-triggered neutrophil differentiation. The failure of G-CSF to induce GADD45β in CN patients might be a reason for the maturation arrest of granulopoiesis.No relevant conflicts of interest to declare.